Digital Implementation Through Interactive Learning Media Wordwall Multiplication Material for Grade III Elementary School - Salma Nanda Ardelia; Gloria Yulianti; Marhamatus Sa'adah; Putri Zudhah Ferryka (Konsienti : Community Services Journal, 2026)
Mathematics learning in elementary schools faces challenges in understanding multiplication concepts due to their abstract nature, requiring interactive media to support Merdeka Curriculum implementation. This study aims to develop interactive Wordwall media to enhance grade III students' multiplication comprehension. Employing Participatory Action Research (PAR), the population comprised all grade III students with a purposive sample of 25 struggling learners. Instruments included observation sheets, questionnaires, Wordwall results, and pre-post tests, analyzed through mixed methods of triangulation and percentage improvement. Results demonstrated significant increases in participation, motivation, and conceptual understanding following five implementation stages. It is concluded that integrating Wordwall with concrete windmill aids effectively transforms rote learning into critical thinking, recommended for elementary teacher adoption.